Hemofílicos com inibidor. Experiência do Centro de Acção Médica de Hemofilia do Hospital de S. José. - M J Diniz; F Dias Francisco; M L Tavares; I Leal (Acta Médica Portuguesa, 1992)
Factor VIII inhibitors arise in 5% to 15% of patients with hemophilia A in response to infusion to factor VIII concentrates and make the treatment of bleeding episodes extremely difficult. Various therapeutic approaches have been tried the decision depending on the type of haemorrhage, the antibody's titre and whether the patient has a low or high response. We report the clinical experience in 13 hemophiliacs with inhibitors to factor VIII. Prothrombin complex concentrates were administered with favorable effects in the most common haemorrhagic episodes, in the majority of patients. In two patients activated prothrombin complex concentrates were administered and in one case plasma exchange was made before high doses of factor VIII. These therapeutic approaches proved to be very effective in the control of hemostasis.